Collaborate - Sanker, Dan, 1965- (Tantor Media, Inc., 2020)
Collaboration is not a new concept, but globalization and new technologies have turned it into one of the best methods of competitive advantage available. Rather than engaging in an endless tug-of-war over the dwindling crumbs in a finite market, collaborative companies find ways to make the pie bigger, or create whole new pies, expanding everyones market and revenue. By collaborating, companies can tap into talent sources beyond their means, overcome organizational weaknesses cheaply by combining capabilities, eliminate waste and overhead by sharing resources, and better engage their markets by providing a more comprehensive and integrated array of products and services. The authors company, CaseStack, is a model of collaboration. Its a full-service logistics company that offers warehousing, transportation and an award-winning tech platform, without owning any actual warehouse buildings or trucks, and using cloud-based hardware. Many of its key business partners could easily be construed as competitors, and its most important service platforms have been developed with retailers who arent customers, vendors, or even partners, in a legal sense. Yet by sharing strengths, all have seen greater profits while cutting costs and improving service. This book shows how others can successfully pool resources and competencies, develop new innovative products and services, access new markets, and reduce costs through collaboration. It explores the tools that facilitate the collaborative process, particularly new online tools that have revolutionized the process, and the outsourcing boom. Case examples illustrate both large-scale (e.g. Disney and McDonalds partnering with Happy Meals) and small-scale collaborations that have succeeded in the real world.